Enhanced compaction and reordering procedure for transition fault testing - Mohan, Navya; P. Anita, J (International Journal of Engineering and Technology, 2018)
Compaction procedure, used to reduce test power, can be efficiently applied on test cubes or incompletely specified tests. This paper demonstrates an improved static compaction and switching activity based test vector reordering methodology which can be applied on a test set that contains both skewed load and broadside tests for transition faults. This compaction procedure goes beyond the normal test vector merging approach generally employed in testing circuits. Here a test is combined with several other tests even if they are not compatible. After obtaining a compact test set, the vectors are reordered such that the total switching activity of the circuit including all the internal nodes is reduced. The simulation results show a considerable reduction in the number of tests and as the test volume reduces the test power also decreases. An average 28.6% reduction in number of test vector pairs is observed as compared to existing static compaction methods and 30.6% reduction in average switching activity (ASA) after reordering.Â Â Â